Dispersões sólidas de sinvastatina: preparação, caracterização, no estado sólido utilizando técnicas emergentes e estudo de estabilidade - Vargas, Mara Rúbia Winter de (2014)
This thesis aimed to assess the increase in solubility of simvastatin (SINV) with solid dispersions using techniques such as kneading (MA), co-solvent evaporation (ES), melting carrier (FC) and spray dryer (SD). Soluplus (SOL), PEG 6000 (PEG), PVP K-30 (PVP) e sodium lauryl sulphate (LSS) were used as carriers. The solid dispersions containing PEG [PEG-2(SD)], Soluplus [SOL-2(MA)] and sodium lauryl sulphate [LSS-2(ES)] were presented with a greater increase in solubility (5.02, 5.60 and 5.43 times respectively); analyses by ANOVA between the three groups did not present significant difference (p<0.05). In the phase solubility study, the calculation of the Gibbs free energy (ΔG) revealed that the spontaneity of solubilisation of SINV occurred in the order SOL>PEG >PVP 75%>LSS, always 80%. The phase diagrams of PEG and LSS presented solubilization stoichiometry of type 1:1 (type AL). The diagrams with PVP and SOL tend to 1:2 stoichiometry (type AL + AP). The stability coefficients (Ks) of the phase diagrams revealed that the most stable reactions occurred with LSS and PVP. The solid dispersions were characterized by Fourier transform infrared (FTIR), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), particle size distribution (PSD), near-infrared spectroscopy imaging (NIR-CI) and X-ray diffraction of the powder using the Topas software (PDRX-TOPAS). The solid dispersion PEG-2(SD) presented the greatest homogeneity and the lowest degree of crystallinity (18.2%). The accelerated stability study revealed that the solid dispersions are less stable than SINV, with PEG-2(SD) being the least stable, confirmed by FTIR and DSC. The analyses by PDRX-TOPAS revealed the amorphous character of the dispersions and the mechanism of increasing solubility